2015
DOI: 10.1123/jsr.2014-0156
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ankle Taping to Restrict Plantar Flexion on Ball and Foot Velocity During an Instep Kick in Soccer

Abstract: Plantar-flexion-limiting taping at 30° has a potential to prevent posterior ankle impingement without decreasing the ball velocity generated by soccer instep kicks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…72 As research progressed, a common finding was that ankle tape restricts ankle range of motion. 5,9,28,[30][31][32]34 In particular, plantarflexion and inversion can be restricted with the ankle tape. 5,9,28,[30][31][32]34 This is noteworthy as the combined motions of plantarflexion and inversion represent the most common positions for ankle sprains.…”
Section: Ankle Tapingmentioning
confidence: 99%
See 4 more Smart Citations
“…72 As research progressed, a common finding was that ankle tape restricts ankle range of motion. 5,9,28,[30][31][32]34 In particular, plantarflexion and inversion can be restricted with the ankle tape. 5,9,28,[30][31][32]34 This is noteworthy as the combined motions of plantarflexion and inversion represent the most common positions for ankle sprains.…”
Section: Ankle Tapingmentioning
confidence: 99%
“…He found that plantarflexion was resisted by 4.18 degrees, dorsiflexion by 3.31, inversion by 5.81 degrees, and eversion by 6.39 degrees. 9 In most recent research, Sasadai 28 looked at the effect of ankle taping and performance with kicking a soccer ball. He found that the tape did restrict maximal plantarflexion needed for the instep of a soccer kick.…”
Section: Ankle Tapingmentioning
confidence: 99%
See 3 more Smart Citations